ANALISIS FAKTOR KOMPLAIN PASIEN DI RUMAH SAKIT KHUSUS DAERAH IBU & ANAK PERTIWI MAKASSAR TAHUN 2023 - Asharandy Rahman; Nurmulia Wunaini Ngkolu; Adriyana Adevia Nuryadin; Ricky Perdana Poetra (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2025)
Complaining behavior is a process of displaying consumers' own experiences that can cause dissatisfaction. Because if you ignore it, you will feel ignored and end up leaving the company. The company/institution must then really look for a way out/solution to resolve customer complaints. The general aim of this research is to analyze the factors of patient complaints at the Pertiwi Regional Special Hospital for Women and Children in Makassar in 2023. The research method used in this research is descriptive qualitative. This research was conducted at the Pertiwi Regional Special Hospital for Women and Children, Makassar. This research was conducted in August 2023 with a total of 7 resondents. Data collection was obtained through in-depth interviews with informants based on interview guidelines. The research results are presented in the form of questions and narratives. Based on the results of research conducted at the Pertiwi Makassar Regional Women's and Children's Special Hospital, there are differences of opinion regarding when patients receive services and when patients submit complaints, officers immediately handle the complaints quickly. When a patient wants to convey their complaint, there is a QR that can be scanned and then fill in the form to submit their complaint. There is also a banner for the flow of patient complaints. The officers also try to help patients if they don't know how to channel this complaint. The suggestion from the result of the research that has been carried out is to pay more attention to every complaint from patient who have undergone treatment, as well as increase responsiveness and speed in providing services.